Photocatalytic activity of magnetic noble metalsdoped coral-like bismuth ferrite nanocomposite for synthetic and real wastewater degradation under visible light and natural sunlight irradiation - Zeeshan, Haider Jaffari (2019)
Industrial wastewater effluents, including malachite green (MG) dye and phenol, are the source of environmental hazards, which required proper attention. Heterogeneous photocatalysis using three dimensional (3D) noble metals-doped magnetic bismuth ferrite (NM-doped BFO) nanocomposite has been developed as an efficient route for the degradation of MG dye and phenol. In the current study, 3D coral-like NM-doped BFO nanocomposite were synthesized using two-steps hydrothermal synthesis method. The structural, morphological, optical and magnetic properties of as-synthesized nanocomposite were analyzed using X-ray diffraction (XRD), Field emissionscanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDX), Transmission electron microscopy (TEM), UV–Vis diffuse reflectance spectra (DRS), photoluminescence (PL), Fourier transform infrared (FTIR) and magnetic hysteresis (M−H) loop analyses. The XRD analysis exhibited the single-phase rhombohedral perovskite structure with high crystallinity. FESEM and TEM images revealed the distribution of metallic noble metals on the surface of coral-like BFO with the diameter ranging from 110 to 130 nm. UV– Vis DRS showed a red-shift on the light absorption edges after the loading of metallic noble metals. FTIR spectroscopy studies confirmed the presence of metallic noble metals and Fe−O bond of FeO6 octahedral perovskite structure. In comparison with the pure BFO, the PL spectra of NM-doped BFO nanocomposite exhibited a dramatic declined in their intensity and the 2 wt% Pd-BFO nanocomposite had the lowest of all, suggesting the lowest recombination rate of electron-hole (e −−h + ) pairs. The photocatalytic activities of as-synthesized noble metals-doped BFO nanocomposite were investigated towards the degradation of MG dye and phenol under visible light irradiation. The photocatalytic results presented that the noble metals-doped BFO nanocomposite exhibited boosted visible light photocatalytic activity on the degradation of MG dye and phenol. Especially, the 2 wt% Pd-BFO nanocomposite displayed the highest photocatalytic activity than that of the pure BFO, 2 wt% Pt-BFO, 2 wt% Ag-BFO as well as commercial TiO2. The enhanced photoactivity was attributed to highest work function value of metallic Pd that could improve the light absorbance in the visible region and photogenerated e −−h + pairs separation/migration abilities as confirmed by the UV-vis DRS and PL analyses. Moreover, the photocatalytic mechanism was purposed with the help of radical scavenger and terephthalicphotoluminescence (TA-PL) studies. The radical scavengers studies demonstrated that the hole (h + ), hydrogen peroxide (H2O2) and hydroxyl (•OH) radicals were the key reactive oxygen species, while the superoxide anion (•O2 − ) exhibited lesser extent. Among the 2 wt% NM-BFO nanocomposite, the PdBFO nanocomposite presented the best heterojunction, led to the highest e −−h + pairs separation efficiency as well as an improvement to generate •OH radicals to some extent. Several process parameters including intensity of light, catalyst loading, initial substrate concentration, solution pH, humic acid and different anion present in wastewater were also investigated. The extent of degradation and mineralization of MG dye and phenol was further verified using chemical oxygen demand (COD). The cyclic test showed that the Pd-BFO nanocomposite has excellent recyclable ability together with a minimal leakage of palladium ions after six runs. The kinetics studies of the MG dye and phenol degradation over 2 wt% Pd-BFO nanocomposite were well fitted by first-order reaction kinetics based on the Langmuir-Hinshelwood model. The electrical energy per order (EEO) calculation for MG dye and phenol degradation suggested that the 2 wt% Pd-BFO nanocomposite was much better than those of the pure BFO and commercial TiO2. Under direct sunlight irradiation, considerably higher photocatalytic activities were also witnessed over 2 wt% Pd-BFO nanocomposite in comparison with the pure BFO and commercial TiO2. Finally, the Pd-BFO nanocomposite was utilized towards the degradation of real textile wastewater, and the consequence showed that the Pd-BFO nanocomposite was also equally effective towards the degradation of real textile wastewater.